Familial Hemiplegic Migraine With Progressive Cerebellar Ataxia Caused by a p.Thr666Met CACNA1A Gene Mutation in a Chinese Family - Li, Mengmeng; Zheng, Xiangyu; Zhong, Rui; Zhao, Qian; Lu, Yingxue; Wang, Zan; Lin, Weihong (Frontiers in Neurology, 2019)
Here, we describe the first case of familial hemiplegic migraine type 1 (FHM1) resulting from a T666M mutation in the CACNA1A gene of a Chinese individual. A 54-year-old female patient demonstrated extensive clinical manifestations, including transient paropsia, hemianesthesia, logaphasia, hemiplegia, migraine, fever, impaired consciousness and progressive cerebellar ataxia. At admission, neurological examination showed a fever of 38.6 ℃, coma, bilateral pupillary constriction, left-sided deviation of both eyes, meningeal irritation and bilateral positive Chaddock’s sign. Brain magnetic resonance imaging (MRI) displayed only cerebellar atrophy. The pressure and white blood cells of the cerebrospinal fluid (CSF) were elevated. Her nine relatives also had similar clinical spectra. To further clarify the diagnosis, we conducted a genetic analysis on the family. The results of genetic testing showed that all seven living affected members carried the T666M mutation in the CACNA1A gene. This case report indicates that the diagnosis of FHM should be taken into account when a patient manifests migraine accompanied with hemiplegia, acute encephalopathy and abnormal CSF. In addition, genetic testing is indispensable for the identification of some atypical attacks of hemiplegic migraine.